Angiographic embolization for hemorrhage following pelvic fracture: Is it "time" for a paradigm shift?. Issue 1 (January 2017) - Tesoriero, Ronald Brian; Bruns, Brandon R.; Narayan, Mayur; Dubose, Joseph; Guliani, Sundeep S.; Brenner, Megan L.; Boswell, Sharon; Stein, Deborah M.; Scalea, Thomas M.
Abstract : Introduction: Major pelvic disruption with hemorrhage has a high rate of lethality. Angiographic embolization remains the mainstay of treatment. Delays to angiography have been shown to worsen outcomes in part because time spent awaiting mobilization of resources needed to perform angiography allows ongoing hemorrhage. Alternative techniques like pelvic preperitoneal packing and aortic balloon occlusion now exist. We hypothesized that time to angiographic embolization at our Level 1 trauma center would be longer than 90 minutes. Methods: A retrospective review was performed of patients with pelvic fracture who underwent pelvic angiography at our trauma center over a 10-year period. The trauma registry was queried for age, sex, injury severity score, hemodynamic instability (HI) on presentation, and transfusion requirements within 24 hours. Charts were reviewed for time to angiography, embolization, and mortality. Results: A total of 4712 patients were admitted with pelvic fractures during the study period, 344 (7.3%) underwent pelvic angiography. Median injury severity score was 29. Median 24-hour transfusion requirements were five units of red blood cells and six units of fresh frozen plasma. One hundred fifty-one patients (43.9%) presented with HI and 104 (30%) received massive transfusion (MT). Median time to angiography was 286 minutes (interquartile range, 210–378). Times were significantly shorter when stratified for HI (HI, 264 vs stable 309 minutes; p = 0.003), and MT (MT, 230 vs non-MT, 317 minutes; p < 0.001), but still took nearly 4 hours. Overall mortality was 18%. Hemorrhage (35.5%) and sepsis/multiple-organ failure (43.5%) accounted for most deaths. Conclusion: Pelvic fracture hemorrhage remains a management challenge. In this series, the median time to embolization was more than 5 hours. Nearly 80% of deaths could be attributed to early uncontrolled hemorrhage and linked to delays in hemostasis. Earlier intervention by Acute Care Surgeons with techniques like preperitoneal packing, aortic balloon occlusion, and use of hybrid operative suites may improve outcomes. Level of Evidence: Therapeutic study, level V.